Strategi Pembelajaran Tahfidz Al-Qur’an di Boarding School dalam Meningkatkan Kualitas Hafalan Santri - Hudallah, Hudallah; Subando, Joko (TSAQOFAH, 2026)
This study aimed to analyze the learning strategies for tahfidz Al-Qur’an at the boarding school MI Miftahut Thulab, as well as the factors that support and hinder the improvement of students’ memorization quality. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings show that the tahfidz learning strategy is implemented through three main stages: planning, implementation, and evaluation. The planning stage includes setting memorization targets adjusted to students’ educational level and initial ability, preparing daily schedules, selecting the methods talaqqi, tikrar, and muroja’ah, and determining memorization quality standards. The implementation stage is supported by a conducive boarding school environment that enables students to internalize routines of worship and tahfidz consistently. The evaluation stage is conducted in a tiered manner to monitor the fluency, accuracy, and consistency of memorization. The study also found supporting factors, including a conducive learning environment, the competence of teachers and musyrif, structured planning, as well as students’ motivation and parental support, all of which play an important role in improving memorization quality. Inhibiting factors include differences in students’ initial abilities, limited time, fatigue or boredom, and inadequate supporting facilities. In conclusion, the success of tahfidz Al-Qur’an learning is highly dependent on the integration between systematic instructional strategies and the management of supporting and inhibiting factors, enabling students to achieve their memorization targets effectively, consistently, and sustainably.